PENGARUH BRAND IMAGE, HARGA DAN KUALITAS PRODUK TERHADAP LOYALITAS PELANGGAN PADA PANCONG SOSIAL SURABAYA - Kurniawati, Ony; Adi, Titok Waskito; Ningrum, Maulidya Rusnita (STIE Mahardhika, 2024)
This study aims to examine and analyze the partial and simultaneous effects of Brand Image, Price, and Product Quality on Customer Loyalty at Pancong Sosial Surabaya. The type of research used is quantitative research with a quantitative descriptive analysis method. The population in this study includes all customers of Pancong Sosial Surabaya. The sampling technique used is non-probability sampling with accidental sampling method. The sample size was determined using the Hair et al. formula, resulting in 70 respondents as the research sample. The results of the t-test indicate that the variables Brand Image and Price have a positive and significant partial effect on Customer Loyalty, while the Product Quality variable has no positive and significant partial effect on Customer Loyalty. Meanwhile, the F-test results show that Brand Image, Price, and Product Quality simultaneously have a significant effect on Customer Loyalty. The coefficient of determination (R²) shows that the variables Brand Image (X1), Price (X2), and Product Quality (X3) together influence Customer Loyalty by 60.8%. The remaining 39.2% is influenced by other variables outside of this regression equation.